The poverty of growth with interdependent utility functions - John Komlos; Peter Salamon (Center for Economic Studies and ifo Institute (CESifo), 2005)
We argue that with interdependent utility functions growth can lead to a decline in total welfare of a society if the gains from growth are sufficiently unequally distributed in the presence of negative externalities, i.e., envy.
Keywords: D63; D62; O00; D64; 330; interdependent utility functions; growth; inequality; Wirtschaftswachstum; Verteilungskonflikt; Nutzenfunktion; Konsuminterdependenz; Theorie